Dukungan Sosial Guru dan Self Regulated Learning Siswa - Tadeus Tea; Dian Lestari Anakaka; Fredericksen Amseke (Journal of Health and Behavioral Science, 2020)
The purpose of this study was to find the level of relationship of teacher's social support with self regulated learning of SMP Abdi Kasih Bangsa Kupang students. 58 students of SMP Abdi Kasih Bangsa Kupang was participated. Self regulated learning scale and teacher social support scale was used to collect data. Pearson correlation product moment was used to see the correlation between the two variables. The results showed that the correlation coefficient (rxy) was 0.424 with a significance value (p) of 0.001 which means there is a relationship between teacher social support and self-regulated learning.